Про подільність спільних кратних матриць третього порядку над комутативними областями безу стабільного рангу 1.5 - Romaniv, A. M.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
Over commutative Bezout domains of stable range 1.5 for nonsingular matrices of the third order, under certain restrictions on invariant factors, the relationship between the divisibility of common right multiples of the matrices and invariant factors of the matrices and their multiples are established. Cite as: A. M. Romaniv, “On the divisibility of common multiples of matrices of the third order over commutative Bezout domains of stable range 1.5,” Prykl. Probl. Mekh. Mat., Issue 22, 31–36 (2024) (in Ukrainian), https://doi.org/10.15407/apmm2024.22.31-36